Remnants of the ancien régime: renomination and re-election of former members of a demised ruling party in Ukraine. Issue 7 (3rd October 2022) - Torikai, Masatomo
ABSTRACT: Although much scholarly attention has recently been devoted to authoritarian successor parties, most existing studies have not empirically examined the survival patterns of former elite cadres of overthrown regimes. This study explores the conditions under which members of former ruling parties survive in the elections that follow the collapse of authoritarian regimes. Exploiting the comprehensive data of 450 incumbents of the national legislature and 2869 incumbents of the regional legislatures in Ukraine, this study examines the survival of the former members of a collapsed ruling party, the Party of Regions (PoR), and demonstrates that former PoR deputies with individual resources, such as those elected in single-member districts, were more likely to secure seats in the subsequent elections. Additionally, electoral calculations prevailed over political programmes or ideologies in terms of party affiliations of former PoR deputies. These findings highlight the importance of individual resources of ex-members of authoritarian ruling parties in political survival.